Transcriptome sequencing and annotation of the testate amoeba Arcella intermedia: Pathway description and gene discovery - Ribeiro, Giulia Magri (2018)
Arcella Ehrenberg 1832 is one of the most numerous testacean genera. Arcellinids are an aerobic lineage of testate amoeba that live in a wide variety of environments. Probably their ability to survive in such divergent conditions is related to some de- gree of metabolic flexibility. Anaerobic organisms have gained and lost a number of genes related to energetic metabolism. These processes modify classic mitochondria until loss of function and transformation in mitochondrial related organelles (mitosomes and hydrogenosomes). Here I propose that Arcella intermedia adaptation to microarophilic environments is related to the acquisition of new genes. There are two main modes of acquisition of new genes. The traditional view, where duplication is followed by mutations and neo-functionality of the duplicate. Or genes can be acquired from other species (lateral gene transfers). The second process has a major importance in prokaryotic evolution and is probably under considered in eukaryotic evolution. I also propose in this work that genes related to anaerobic metabolism in Arcella are acquired by lateral gene transfer. However, analysis of genomic and transcriptomic data are absent for A.intermedia. Characterizing genome-scale data from eukaryotes is essential for gene discovery and for inferring transitions over the tree of life. The transcriptome dataset from this work provides the first effort of characterization of expressed sequences in A.intermedia. We used single cell from different moments of growth and whole culture RNA extraction in order to increase the diversity of metabolic moments of the cells. Mapped sequences allowed us to identify functional pathways in A.intermedia cells. In general, it seems that metabolic processes are showing up more, followed by signaling and responses to stimuli. We describe functioning of carbohydrate and energy metabolism including even an anaerobic pathway to produce energy. We found ACS-ADP and PFO genes in A.intermedia. We describe amino acid metabolism, with at least 12 amino acids metabolizing pathways described and catabolism mainly related to TCA cycle intermediates. Calcium, Ras GTPases, PI3K-AK and AMPK-mTOR are the main signaling pathways represented in transcriptomes. We described important pathways for amoeba: endocytosis and phagocytosis and it seems to be similar with the ones already described for other amoeba with a dependence on F-actin and small GTPases of Rho subfamily. We couldn\'t find lots of information about programmed cell death in A.intermedia, however cell growth are similar to pathways described for dinoflagellates. We expect that upcoming genomes will finish the description of functioning of those organisms, but we believe our work already is a good starting point. In order to gain a clearer picture of the presence of anaerobic metabolism genes in Amoebozoa, we conducted BLAST searches in Amoebozoa and Arcellinida data bases for the presence/absence of ACS-ADP, PFO and [FeFe]-H2ase. Other Arcellinida species also presented these genes, Difflugia sp., Difflugia compressa and Cyclopyxis lobostoma. Besides these, the already known Mastigamoeba balamuthi, Entamoeba histolytica and Acanthamoeba castelanii. Amoebozoa sequences don\'t form a monophyletic group in any of the three genes. However, Arcellinida sequences always grouped together. As such distinct amoeba groups have those anaerobic metabolism genes, however, most of the Amoebozoa do not. It is more likely to think of lateral transfers occurring independently among these amoeba groups, generating the possibility of occupying a new niche. The main objective of this work was to start generating tools to understand the ability of some testate amoeba to resist environmental harsh conditions. We found lots of interesting questions but the one we focused on this dissertation was (1) the evolution of anaerobic related genes in testate amoeba lineages. The assembled and annotated sequence data will be available as reference sequences, making the work with this group easier. The results can also potentially be applied as biomonitoring markers for the management of water resources. This work will improve the general knowledge on the evolution and function of freshwater organisms. We expect also to make a contribution on the understanding of the impact of lateral gene transfers in Arcellinida diversity